Combustion of High-Energy Compositions (HECs) Containing Al-B, Ti-B and Fe-B Ultrafine Powders (UFPs) - Weiqiang Pang; Ivan Sorokin; Alexander Korotkikh (Nanomaterials)
Metal and metalloid powders are widely used in high-energy compositions (HECs) and solid propellants (SPs), increasing their energetic characteristics in the combustion chamber. The particle size distribution, protective coatings of the particles and heat of combustion of the metal powders influence the ignition and combustion parameters of the HECs as well as the characteristics of the propulsion systems. Boron-based metallic fuels achieve high-energy potentials during their combustion. The effect of Al-B, Fe-B and Ti-B (Me-B) mixture ultrafine powders (UFPs) on the ignition and combustion characteristics of a model HEC based on a solid oxidizer and a polymer combustible binder was investigated. The Me-B mass ratios in the mixture UFPs corresponded to the phase composition of the borides AlB2, FeB and TiB2. It was found that replacing the aluminum UFP with Al-B, Fe-B and Ti-B UFPs in the HECs changed the exponent (n) in the correlations of the ignition delay time tign(q) and burning rate u(p). The maximum burning rate and n over the pressure range of 0.5–5.0 MPa were obtained for the HEC with Al-B UFPs due to the increase in the heat release rate near the sample surface during the joint combustion of the Al and B particles.